The Effect Of Virtual Reality On Pain In Diabetic Foot Ulcer Patients - Baidhowy, Arief Shofyan; Nurhaslina Rahmah, Irma; Khoiriyah, Khoiriyah; Rejeki, Sri (Chakra Brahmanda Lentera Institute, 2024)
Background: Diabetes Mellitus (DM) is a heterogeneous group of disorders characterized by increased blood glucose levels or hyperglycemia which can cause complications such as Diabetic Foot Ulcer. Debridement can cause the patient to experience pain. A nursing intervention that can be used to reduce pain during the debridement of diabetic ulcers is a distraction. VR (Virtual Reality) become a popular distraction device to reduce pain. The purpose of this study was to analyze the effect of Islamic audio-visual therapy by using virtual reality on pain in the treatment of diabetic ulcers. Methods: This type of research uses a quantitative research type with Quasi-experimental with the One Group Pre-Post Test Design approach. The population in this study were diabetes mellitus ulcer pain patients at the Semarang Foid Clinic with a total of 26 patients with a total sample using 26 samples. The instrument used was the pain observation sheet. Data analysis used the Wilcoxon test. Results: the majority were male 65.4%, the majority had a high school education 42.3%, the majority suffered 1-2 months 73.1% and the majority had a grade I Diabetes Mellitus ulcer 65.4%. The results of p-value 0.001 <0.05 can be interpreted that there is an effect of Islamic audio-visual therapy on pain in diabetic ulcer care. Conclusion: This study provides an effect of Islamic audio-visual therapy by using virtual reality on pain in diabetic ulcer care. VR has an effective effect on lower pain in DFU patients. In future research, more detailed criteria are required, such as patients with similar diseases, same age group, and more participants to study.